2015
DOI: 10.1642/auk-14-77.1
|View full text |Cite
|
Sign up to set email alerts
|

Birds build camouflaged nests

Abstract: It is assumed that many birds attempt to conceal their nests by using camouflage. To our knowledge, however, no previous experimental studies have explicitly tested this assumption. To explore whether birds choose materials that match the background colors of nest sites to reduce the conspicuousness of their nests, we offered nest-building male Zebra Finches (Taeniopygia guttata) a choice of nest materials that either matched or did not match the color of their nest cup and the surrounding cage walls. Males ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 26 publications
0
38
0
1
Order By: Relevance
“…Turning to homes built by animals, Bailey et al . () provide evidence that birds may actively select materials that camouflage their nests. They demonstrate that captive zebra finches ( Taeniopygia guttata ) preferentially select nesting material that is similar in colour to the provided nest cup and surrounding cage walls.…”
Section: Decoration and Background Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Turning to homes built by animals, Bailey et al . () provide evidence that birds may actively select materials that camouflage their nests. They demonstrate that captive zebra finches ( Taeniopygia guttata ) preferentially select nesting material that is similar in colour to the provided nest cup and surrounding cage walls.…”
Section: Decoration and Background Modificationmentioning
confidence: 99%
“…Almost by definition, traps such as spider's webs must be constructed in such a way as to be difficult for prey to detect in order to be effective, and there is evidence that certain specific features of webs can be linked to reduced avoidance by prey [see Théry & Casas, 2009 for a review]. Turning to homes built by animals, Bailey et al (2014) provide evidence that birds may actively select materials that camouflage their nests. They demonstrate that captive zebra finches (Taeniopygia guttata) preferentially select nesting material that is similar in colour to the provided nest cup and surrounding cage walls.…”
Section: (3) Hiding Built Structuresmentioning
confidence: 99%
“…Studies investigating the cognitive processes underlying nest construction suggest that captive Zebra Finches (Taeniopygia guttata) have an appreciation of physical characteristics of the materials they use in their nests (Bailey et al, 2014a(Bailey et al, , 2014b. Moreover, studies that deconstruct nests have shown that the characteristics of the various materials in different parts of the nest provide an indirect insight into the decisions made by birds during nets building.…”
Section: Robins Nest In Enclosed Areas or Within Open-fronted Nestboxmentioning
confidence: 99%
“…Whilst the nest itself is primarily where eggs are incubated (Deeming 2016) it is suggested that they have a range of other roles associated with reproduction, and perhaps even lifetime fitness (Moreno 2012;Mainwaring et al 2014a). Birds select materials during nest construction for a variety of reasons (Deeming and Mainwaring 2015), including sexual signalling (Dubiec et al 2013;Tomás et al 2013), defence from parasites or pathogens (Dubiec et al 2013), camouflage (Kull 1977;Bailey et al 2015), insulation (Hilton et al 2004;Dhandhukia and Patel 2012;Mainwaring et al 2014b) or for their structural role (Bailey et al 2014;Biddle et al 2015Biddle et al , 2017. Whether these materials are deliberately selected for specific roles has yet to be fully investigated, but it is known that variation in a particular type of material reflects its availability within the local environment (Moreno et al 2008;Surgey et al 2012;Álvarez et al 2013;Cantarero et al 2015;Briggs and Deeming 2016).…”
Section: Introductionmentioning
confidence: 99%